Hostile attitudes and effortful coping in young adulthood predict cognition 25 years later. (29th March 2016) - Albanese, Emiliano; Matthews, Karen A.; Zhang, Julia; Jacobs, David R.; Whitmer, Rachel A.; Wadley, Virginia G.; Yaffe, Kristine; Sidney, Stephen; Launer, Lenore J.
Abstract : Objective: We studied the relation of early-life (mean age 25 years) and mid-life (mean age 50 years) cognitive function to early measures of hostile attitudes and effortful coping. Methods: In 3, 126 black and white men and women (born in 1955–1968) from the Coronary Artery Risk Development in Young Adults Study (CARDIA), we used linear regression to examine the association of hostile attitudes (Cook-Medley questionnaire) and effortful coping assessed at baseline (1985–1986) to cognitive ability measured in 1987 and to a composite cognitive Z score of tests of verbal memory, psychomotor speed, and executive function ascertained in midlife (2010–2011). Results: Baseline hostility and effortful coping were prospectively associated with lower cognitive function 25 years later, controlling for age, sex, race, education, long-term exposure to depression, discrimination, negative life events, and baseline cognitive ability. Compared to the lowest quartile, those in the highest quartile of hostility performed 0.21 SD units lower (95% confidence interval [CI] −0.39, −0.02). Those in the highest quartile of effortful coping performed 0.30 SD units lower (95% CI −0.48, −0.12) compared to those in the lowest quartile. Further adjustment for cumulative exposure to cardiovascular risk factors attenuated the association with the cognitive composite Z score for hostility. Conclusions: Worse cognition in midlife was independently associated with 2 psychological characteristics measured in young adulthood. This suggests that interventions that promote positive social interactions may have a role in reducing risk of late-age cognitive impairment.